Air Pollution’s Impact on Cardiac Remodeling in an Experimental Model of Chagas Cardiomyopathy - Fonseca, Keila Cardoso Barbosa; Pessoa, Fernanda Gallinaro; Ribeiro, Orlando do Nascimento; Hotta, Viviane Tiemi; Ianni, Barbara Maria; Fernandes, Fabio; Ferreira Rivero, Dolores Helena Rodriguez; Saldiva, Paulo Hilário Nascimento; Mady, Charles; Ramires, Felix José Alvarez (Frontiers in Cellular and Infection Microbiology, 2022)
Background Chagas disease is characterized by intense myocardial fibrosis stimulated by the exacerbated production of inflammatory cytokines, oxidative stress, and apoptosis. Air pollution is a serious public health problem and also follows this same path. Therefore, air pollution might amplify the inflammatory response of Chagas disease and increase myocardial fibrosis. Methods We studied groups of Trypanosoma cruzi infected Sirius hamsters (Chagas=CH and Chagas exposed to pollution=CH+P) and 2 control groups (control healthy animals=CT and control exposed to pollution=CT+P). We evaluated acute phase (60 days post infection) and chronic phase (10 months). Echocardiograms were performed to assess left ventricular systolic and diastolic diameter, in addition to ejection fraction. Interstitial collagen was measured by morphometry in picrosirius red staining tissue. The evaluation of inflammation was performed by gene and protein expression of cytokines IL10, IFN-γ, and TNF; oxidative stress was quantified by gene expression of NOX1, MnSOD, and iNOS and by analysis of reactive oxygen species; and apoptosis was performed by gene expression of BCL2 and Capsase3, in addition to TUNEL analysis. Results Chagas groups had increased collagen deposition mainly in the acute phase, but air pollution did not increase this deposition. Also, Chagas groups had lower ejection fraction in the acute phase (p = 0.002) and again air pollution did not worsen ventricular function or dilation. The analysis of the inflammation and oxidative stress pathways were also not amplified by air pollution. Apoptosis analysis showed increased expression of BCL2 and Caspase3 genes in chagasic groups in the acute phase, with a marginal p of 0.054 in BCL2 expression among infected groups, and TUNEL technique showed amplified of apoptotic cells by pollution among infected groups. Conclusions A possible modulation of the apoptotic pathway was observed, inferring interference from air pollution in this pathway. However, it was not enough to promote a greater collagen deposition, or worsening ventricular function or dilation caused by air pollution in this model of Chagas cardiomyopathy.